2019
DOI: 10.1002/solr.201900273
|View full text |Cite
|
Sign up to set email alerts
|

ITO‐Free Organic Photovoltaic Modules Based on Fluorinated Polymers Deposited from Non‐Halogenated Solution: A Major Step Toward Large‐Scale Module Production

Abstract: Several bottlenecks need to be passed to reach market readiness for organic photovoltaic modules. To avoid scarce and costly materials such as indium is an important technological issue. To be able to process the active layer from solutions prepared from non-halogenated solvents and harmless additives is also a crucial step. Herein, a fluorinated polymer is used as an electron-donor material and PC 71 BM as an electron-accepting material in a bulk-heterojunction configuration, to demonstrate that indium-tin-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
(48 reference statements)
1
12
0
1
Order By: Relevance
“…The aforementioned empirical evaluation can be significantly strengthened through quantitative prediction of the solubilities using the Hansen solubility parameters (HSPs), as demonstrated in various eco-friendly PSC studies. , The HSPs are δ D , δ P , and δ H , which represent dispersive interactions, permanent dipole–dipole interactions, and hydrogen bonding interactions, respectively. The HSPs of a material can be plotted in a 3-dimensional space (Hansen space) where δ D , δ P , and δ H correspond to the x , y , and z axes, respectively.…”
Section: Selection Of Suitable Green Solventsmentioning
confidence: 99%
“…The aforementioned empirical evaluation can be significantly strengthened through quantitative prediction of the solubilities using the Hansen solubility parameters (HSPs), as demonstrated in various eco-friendly PSC studies. , The HSPs are δ D , δ P , and δ H , which represent dispersive interactions, permanent dipole–dipole interactions, and hydrogen bonding interactions, respectively. The HSPs of a material can be plotted in a 3-dimensional space (Hansen space) where δ D , δ P , and δ H correspond to the x , y , and z axes, respectively.…”
Section: Selection Of Suitable Green Solventsmentioning
confidence: 99%
“…PF2 is a recently reported moderate bandgap (E gap ) polymer that has been successfully used to fabricate efficient small size devices and large surface modules. 18,19 It exhibits among other interesting properties, good charge transport properties and high structural stability under thermal treatment. 20 J71 is a 2D conjugated wide E gap polymer that has been used in efficient OPVs by blending with nonfullerene acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 Frederik Krebs [302] reported on the use of opaque bottom electrodes made of Cu(50 µm)/Ti (100 nm) in large area modules illuminated from top. This strategy has since been followed by others [36,100,[303][304][305][306][307][308][309][310][311][312][313][314][315][316] and the list of opaque electrodes tested includes mostly thick (typically ≈100 nm) silver [36,100,[303][304][305][306][307][308][309][310] and aluminum films [311][312][313] among others. [314][315][316] In 2015, Huang et al [100] reported top-illuminated single cells with an active area of 1 cm 2 and with a thick (100 nm) opaque Ag bottom electrode exhibiting a PCE of 7.21%, based on a and c) P3 by shadow mask.…”
Section: Upscaling Using Opaque Bottom Electrodes With Top (Backside) Illuminationmentioning
confidence: 99%
“…Top-illuminated 10 cm 2 NFA-based OPV cells with structure glass/HxMoO 3 /opaque Ag (70 nm)/PAL/HxMoO 3 / ultrathin Ag (8 nm)/MoO 3 , where the PAL consisted of PM6:IT-4F, achieved an impressive PCE of 10.24%. [310] Using an opaque Al film (100 nm thick) as bottom electrode, Ibraikulov et al [313] produced modules of 15 monolithic cells connected in series, based on a blade-coated PAL of PF2:PC 71 BM, with an impressive total active area of 66 cm 2 (GFF = 69%) that achieved a PCE of 6.1%.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%